1980
DOI: 10.1121/1.384627
|View full text |Cite
|
Sign up to set email alerts
|

Temperature variation of the acoustical properties of laboratory sediments

Abstract: The compressional wave speed and attenuation and the shear wave speed and attenuation of unconsolidated artificial laboratory sediments have been measured as a function of temperature. No overburden or pore pressure in excess of that found at a few centimeters depth was applied. The compressional wave speed of the sediment was found to vary approximately as would water. Shear wave speed appears to be independent of temperature within the accuracy of the measurement. Attenuation of both types of acoustic waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…7 Bell and Shirley measured the shear wave speeds in water-saturated sand with the grain size of 0.35 mm at the frequency of 7 kHz. The temperature dependence of the shear wave speed and attenuation depends on the grain size and the measuring frequency.…”
Section: B Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Bell and Shirley measured the shear wave speeds in water-saturated sand with the grain size of 0.35 mm at the frequency of 7 kHz. The temperature dependence of the shear wave speed and attenuation depends on the grain size and the measuring frequency.…”
Section: B Results and Discussionmentioning
confidence: 99%
“…6 Measurements of the speed and attenuation of shear waves have been reported by many researchers. [7][8][9][10][11][12] The relationship of the shear wave speed to the mean grain size, porosity, or depth has been shown in their reports. However, they obtained most of their data at only a single frequency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To make the estimation of clay-bound water (Phiclay*Vcl) even more difficult the petrophysical and acoustic properties of clay minerals vary with temperature (Bell and Shirley, 1980), pressure (Marion, Nur, and Han, 1992), and salinity. The author doesn't have a reference for the effects of salinity on petrophysical properties, but drilling studies show that the strength of shale in wells is affected by the salinity of the drilling mud.…”
Section: Comparing the Methodsmentioning
confidence: 99%
“…Density no longer plays a significant role, and the major factors become pressure, temperature, and frame rigidity. Bell and Shirley (1980) showed that the type of loose material makes no difference to the compressional wave (P-wave) velocity. Talwani et al (1973) showed that loose sediments exhibit hysteresis, that is, the velocity change with increasing pressure is reversible whereas the porosity change is not.…”
Section: Seismic Reflection Theorymentioning
confidence: 99%